PIPADS-a low cost real-time visualization tool - Spray, A.; Schröder, H.; Lie, K. T.; Plesner, E.; Bray, P. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
PIPADS, the Parallel Image Processing and Display System, is an architecture targeted at supporting real-time image processing tasks at low cost. The machine uses an inexpensive semicustom SIMD array which, through supporting scan-line-based algorithms, can produce mega-pixel perspective views of terrains in real-time. This paper presents the constraints placed on the SIMD array, and details the how the architecture and implementation minimize hardware, time and volumetric costs.